Alterations in Enterohepatic Fgf15 Signaling and Changes in Bile Acid Composition Depend on Localization of Murine Intestinal Inflammation. Issue 10 (October 2016) - Rau, Monika; Stieger, Bruno; Monte, Maria J.; Schmitt, Johannes; Jahn, Daniel; Frey-Wagner, Isabelle; Raselli, Tina; Marin, Jose J. G.; Müllhaupt, Beat; Rogler, Gerhard; Geier, Andreas
Abstract : Background: Fibroblast growth factor (FGF) 15/19 is part of the gut-liver crosstalk accounting for bile acid (BA) metabolism regulation. Dysregulation of fibroblast growth factor 15/19 signaling is observed in different pathological conditions, for example, in gastrointestinal diseases such as inflammatory bowel disease (IBD). To understand the molecular bases, we analyzed the enterohepatic regulation of Fgf15-mediated pathway in 2 different inflammatory bowel disease mouse models. Methods: Target genes of the BA-farnesoid-X-receptor (Fxr)-Ffg15 axis were quantified by RT-PCR or western blotting in gut and liver of dextran sulfate sodium (DSS)-treated and IL10 (−/−) mice. Serum Fgf15 levels were analyzed by ELISA. Biliary and fecal BA composition was differentiated by HPLC-MS/MS. Results: Dextran sulfate sodium-treated mice with ileum-sparing colitis showed higher Fgf15 serum levels. In contrast, IL10 (−/−) mice with ileitis had a trend toward decreased Fgf15 serum levels compared with controls and increased expression of Asbt as a negative Fxr-target gene. In hepatic tissue of both models, no histological changes, but higher interleukin 6 (IL-6) mRNA expression and down-regulation of Fxr and Cytochrom P450 7a1 mRNA expression were observed. Fibroblast growth factor receptor 4 up-regulation was in line with higher Fgf15 serum levels in dextran sulfate sodium-treated mice. A distinct fecal BA profile was observed in both models with significantly higher levels of taurine-conjugated BA in particular tauro-β-muricholic acid in IL10 (−/−) mice. Conclusions: Ileum-sparing colitis is characterized by activation of Fxr-Fgf15 signaling with higher expression of Fxr-target gene Fgf15, whereas ileal inflammation showed no signs of Fxr-Fgf15 activation. Abundance of BA such as T-β-MCA may be important for intestinal Fxr activation in mice. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 30 August 2016.